Prominent linguistic features of pedagogical texts to provide consideration for authentic text simplification - Try Mahendra Siregar; Widyastuti Purbani (Universitas Syiah Kuala, 2024)
Teaching materials are significant items that are unique and specific. Therefore, the selections should be relevant to students proficiency. This research aimed (1) to disclose lexical density, readability, nominalizations, and modifiers in pedagogical texts as teaching materials, (2) to reveal the linguistic features functional roles on text for pedagogical demand, and (3) to attempt to suggest consideration for simplification on authentic text. This research employed qualitative content analysis. The data sources were 18 pedagogical texts from senior high school textbooks by the Indonesian Ministry of Education. Human instruments and a text analyser for the automatic computation were utilized for the analysis under Systemic Functional Linguistics (SFL) pilots. This research disclosed the appropriate text lexical density for senior high school students is a fairly difficult construction. Then, nominalizations within the texts are unpreventable and process nominalization is frequently used. The nominalization and the modifiers affect sentence complexities; the nominalizations function to condense information, collocate words, create cohesiveness, interfere with conciseness, and use as trans-categorization while modifiers are to add explicitness to nouns. The simplification considerations are by utilizing lexical density and readability algorithm, de-nominalization, measuring modifiers, and splitting substance of modifiers to increase text accessibility.